Case report: Ureteric bud intestinal-type adenocarcinoma involving the cervix was misdiagnosed as a large cervical fibroid - Zhang, Li-li; Wang, Li; Zhang, Dan-ni; Wu, Jun-tong; Liu, Yuan; Wang, Yan-ping (Frontiers in Medicine, 2024)
Background Malignant tumors of the ureteric bud are not common, and cervical involvement is even rarer. So far, there have been no such cases in the literature. Case summary A 50-year-old woman developed intermittent light bleeding in the past 7 months and lower abdominal pain in the past 2 months. The human papillomavirus 16 (HPV) DNA, P16 chemical staining, thinPrep cytology test (TCT), and cervical and cervical canal tissue biopsy were all negative. Pelvic color Doppler ultrasound exhibited incomplete mediastinal uterus and heterogeneous echo from the cervical canal to the posterior wall of the cervix. Pelvic contrast-enhanced CT showed left cervical mass, left retroperitoneal mass, absence of the left kidney, and mediastinal uterus. An increase in human epididymal protein 4 (HE4) (133.6 pmol/L) was detected, while other tumor markers were at normal levels. Based on these examination results, a diagnosis of “cervical fibroids, left retroperitoneal mass, incomplete mediastinal uterus, left kidney deficiency”[SIC] was conducted, and expanded hysterectomy, right adnexectomy, and left retroperitoneal mass resection were performed. Through intraoperative rapid pathological diagnosis, postoperative pathological diagnosis combined with the re-evaluation of laboratory, and imaging and intraoperative examination results, the patient was diagnosed with ureteric bud intestinal-type adenocarcinoma involving the cervix. The patient has been tracked and followed up for approximately 11 months. She underwent six courses of chemotherapy. At present, the medication has been discontinued for 4 months, and there is no recurrence, metastasis, or deterioration of the tumor. Conclusion For large masses of the cervix, it is feasible for the operation to be performed, improving the prognosis. There were a few limitations. A preoperative aspiration biopsy of masses was not performed to differentiate benign from malignant. Preoperative urography was not performed to clarify the function of the malformed urinary system structure. Partial cystectomy should be performed simultaneously with the resection of the ureteric bud for intestinal-type adenocarcinoma. In this case, a partial cystectomy was not performed, which can only be compensated with postoperative chemotherapy. Moreover, this patient did not undergo genetic screening, and it is currently unclear whether there are any genetic mutations associated with ureteric bud intestinal adenocarcinoma.